A complementary approach to conjugated N-acyliminium formation through photoredox-catalyzed intermolecular radical addition to allenamides and allencarbamates - Koleoso, Olusesan K.; Turner, Matthew; Plasser, Felix; Kimber, Marc C. (Beilstein Journal of Organic Chemistry, 2020)
An intermolecular radical addition, using photoredox catalysis, to allenamides and allencarbamates is reported. This transformation synthesizes N-acyl-N’-aryl-N,N’-allylaminals, and proceeds by a conjugated N-acyliminium intermediate that previously has principally been generated by electrophilic activation methods. The radical adds to the central carbon of the allene giving a conjugated N-acyliminium that undergoes nucleophilic addition by arylamines and alcohols.
Keywords: allenamide; allene; intermolecular; N-acyliminium; photoredox